Exploring Gamification Approaches in Grammar Learning - Minak Inton, Ledy Nur Lely (STIT Buntet Pesantren Cirebon, 2024)
The integration of digital tools into education has fostered innovative methodologies like gamification, which is particularly notable in the field of grammar learning. This literature review assesses the role of gamification—defined as the use of game design elements in educational settings—in enhancing grammar mastery. Traditional grammar teaching often struggles to maintain student engagement and motivation, which are critical for effective learning. This review evaluates the efficacy of gamification in grammar instruction by analyzing empirical studies and scholarly articles from databases including Google Scholar and various educational journals. Focused keywords such as